Akulturasi Penanggalan Jawa Perspektif Islam dalam Kehidupan Para Petani (An Acculturation in the Islamic Perspective of the Javanese Calendar the Lives of Farmers) - Ridho Riyanto; Betty Mauli Rosa Bustam (Institut Agama Islam Negeri (IAIN) Manado, 2022)
This study discusses how the form of acculturation on the use of Javanese calendar media with Islamic culture. The purpose of this study is to describe descriptively how the forms of acculturation that can be done in the Javanese calendar. This research uses the type of literature review research. Where the data collection technique is by browsing documents or journals and other internet media related to cultural acculturation. The results of the research carried out were to obtain information about acculturation to the Javanese calendar after reviewing from various sources, that by incorporating elements of the Islamic religion and Islamic principles in the benefits of the Javanese calendar, it can provide a sense of intolerance to all existing differences.